Correlational Study of the Factors that Influence in the Recommendation and Loyalty of Patients of Aesthetic Medicine Medellín Colombia, 2014 (2017)
ABSTRACT: Aesthetic procedures have gained high relevance within health services offer, becoming consolidated as an attractive market that requires assessment in order to improve its services and thus attracting and keeping its users. This research identified the factors that influence processes of recommendation and loyalty produced within the medic-patient relationship in aesthetic medicine, among which the quality of the relationship, trust, satisfaction and perceived value are addressed. Afterwards, a model of relationships among constructs was proposed, which is contrasted against a sample of 391 patients of Medellin’s (Colombia) metropolitan area. A confirmatory factorial analysis was carried out in order to guarantee the reliability and validity of the measurement scales, which allowed to contrast the hypotheses by means of a structural equations analysis. Once the factorial correlation is revised, proof is shown for the existence of an influence relationship of constructs such as perceived value, satisfaction and the quality of the medic-patient relationship in loyalty, and also that satisfaction and loyalty, in turn, directly influence recommendations.